A new understanding of marketing and "doing good": marketing's power in the TMT and corporate social responsibility - Wenbin, Sun (Journal of business ethics, 2022)
The traditional understanding of corporate social responsibility (CSR) has largely been focused on its downstream performance implications, particularly its associations with firms’ customer market metrics such as customer loyalty, customer satisfaction and customer co-creation as well as financial ones such as firm value, return on assets etc. However, given the close relationship between CSR and marketing that literature has identified, it is surprising that the relationship between a focal upstream construct, i.e. the marketing function’s power within a firm and the firm’s propensity toward CSR has not been addressed in the literature. Examining the link between marketing’s power (MP) in a firm’s top management team (TMT) and firm CSR levels, we investigate how this fundamental TMT configuration, i.e. the distribution of marketing power in the TMT, motivates the firm’s social endeavors. Further, we formulate this relationship in a contingency-based model that incorporates the moderating effects of firm size, firm age, service intensity, and resource slack across 1569 firms operating in 63 industries. In addition to their effect on CSR, this study shows how MP in TMT may influence corporate social irresponsibility (CSI) as well as CSR capability after controlling for industry type. The inclusion on these additional dimensions of CSR (CSI and CSR capability) complements our analyses of the effect that MP has on CSR. The research contributes to a deeper understanding of CSR’s fundamental corporate determinants as well as identifies the essential role of the marketing function in firms’ CSR strategy. In this process, it yields useful implications for multiple streams of theory as well as for business practices.